International Transmission of Interest Rates and the Open Economy Trilemma in Asia - CHOW, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2014)
There has recently been much discussion on the relevance of the open economy trilemma in the context of deepening financial integration of countries across the world (see for instance, Rey (2013) and Devereux and Yetman (2014)). The open economy trilemma is an important issue for the countries in Asia not least because their financial systems are small and exchange rate stability is crucial to their economic growth. This paper investigates whether the economies in Asia are still bound by the "impossible trinity" by examining the interest rate transmission from the US to the region before and after the onset of the global financial crisis. We make a distinction between long-run versus short-run transmission of interest rates by conducting the Peseran bounds test of cointegration and Wald test of joint significance respectively on autoregressive distributed lag models estimated with data from nine Asian economies. The findings on the strength of interest rate pass-through are related to each country's trilemma configuration. Overall, our empirical results provide some supporting evidence that the Asian economies are still constrained by the open economy trilemma.